2012
DOI: 10.1080/10942912.2010.513025
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Protein Hydrolysate from Yellow Stripe Trevally (Selaroides leptolepis)

Abstract: Storage stability of protein hydrolysate from yellow stripe trevally prepared using Flavourzyme with a degree of hydrolysis of 25% (HF 25 ) was determined. During storage, slight increases in water activity and moisture content and a slight decrease in lightness of HF 25 and Bacto Peptone were observed. Generally, browning intensity, A 294 , and fluorescent intensity of HF 25 and Bacto Peptone increased. Both samples had an excellent solubility at pH 5 and 7. Thiobarbituric acid reactive substances in HF 25 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
2
7
1
2
Order By: Relevance
“…The initial TBARS was 0.89 mg malonaldehyde kg -1 which crossed the acceptability limit of 2 mg malonaldehyde kg -1 (Connell, 1990) in the second month (2.19 mg malonaldehyde kg -1 ) under ambient temperature, while it was extended to three months reaching a value of 2.23 mg malonaldehyde kg -1 when stored under chilled conditions (Table 2). In concurrence to these results, Klompong et al (2012) observed a rise in TBARS values in yellow stripe trevally protein hydrolysate stored at room temperature during a storage period of 12 weeks. They further reported higher lipid oxidation possibilities in dried samples on account of the enhanced exposure of lipids present in the sample, to oxygen at a low water level.…”
Section: Tbarssupporting
confidence: 84%
See 2 more Smart Citations
“…The initial TBARS was 0.89 mg malonaldehyde kg -1 which crossed the acceptability limit of 2 mg malonaldehyde kg -1 (Connell, 1990) in the second month (2.19 mg malonaldehyde kg -1 ) under ambient temperature, while it was extended to three months reaching a value of 2.23 mg malonaldehyde kg -1 when stored under chilled conditions (Table 2). In concurrence to these results, Klompong et al (2012) observed a rise in TBARS values in yellow stripe trevally protein hydrolysate stored at room temperature during a storage period of 12 weeks. They further reported higher lipid oxidation possibilities in dried samples on account of the enhanced exposure of lipids present in the sample, to oxygen at a low water level.…”
Section: Tbarssupporting
confidence: 84%
“…pH variations during sample storage is widely assessed for determining its stability. Previously, studies conducted by Klompong et al (2012) reported no marked changes in pH of yellow stripe trevally protein hydrolysate stored for a period of 12 weeks at room temperature.…”
Section: Phmentioning
confidence: 95%
See 1 more Smart Citation
“…Protein degradation that leads to peptides with increased charge density contributes to increased solubility (Wieczorek, Adamala, Gasperi, Polticelli, & Stano, ). Peptides with different biological activities have been recently produced from fish proteins, including seabass (Sae‐leaw et al., ; Sae‐Leaw et al., ), kilka (Zamani, Madani, Rezaei, & Benjakul, ), tilapia (Yarnpakdee, Benjakul, Kristinsson, & Kishimura, ), yellow stripe trevally (Klompong, Benjakul, Kantachote, & Shahidi, ), and sardine (Bougatef et al., ), by enzymatic hydrolysis. Temperature, time, and type and concentration of enzyme are factors affecting the degree of hydrolysis (DH), which is the ratio of the number of the cleaved peptide bonds to the total peptide bonds (Zamani et al., ).…”
Section: Bioactive Peptidesmentioning
confidence: 99%
“…En este trabajo, el hidrolizado elaborado con enzimas de P. muelleri supera ampliamente los valores anteriormente mencionados, alcanzando el 54.36% de EB a los 90 minutos de reacción y, junto con el resto de los hidrolizados, a los 180 minutos llega al 80% de EB. Este último valor coincide con los observados por (KLOMPONG et al, (2012) en el hidrolizado obtenido con enzima Flavourzyme®. Sin embargo, tanto (PIOTROWICZ; MELLADO,…”
Section: Resultados Y Discusiónunclassified